UTOPIAS HELENÍSTICO-ROMANAS - Cardoso, Ciro Flamarion (PHOÎNIX, 2020)
In the ancient Greek world, the construction of imaginary worlds was never absent. Nevertheless, we notice a contrast when comparing such alternate realities as imagined under the reign old polis and the citizenship linked to this form ofslate, to those which appeared later on, in Hellenistic and Roman limes, when citizenship in fact ceased to exist. The paper focuses on the latter: utopias which no longer intended to exert anv influence on politics or social reality, but, on the contrary, built up idealised and rural worlds to which one could escape in spirit for a time. The text studies in some detail the works of three authors: lamboulos (as known through Diodorus Siculus), Lucianus and Longus.